2015
DOI: 10.1007/s12223-015-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial biofilms by diabetic foot clinical isolates

Abstract: Diabetes mellitus is a major chronic disease that continues to increase significantly. One of the most important and costly complications of diabetes is foot ulceration that may be colonized by pathogenic and antimicrobial resistant bacteria, which may express several virulence factors that could impair treatment success. These bacterial communities can be organized in polymicrobial biofilms, which may be responsible for diabetic foot ulcer (DFU) chronicity. We evaluated the influence of polymicrobial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 21 publications
3
59
0
1
Order By: Relevance
“…PVAAA and PVAPR showed significantly higher LDH activity (4.32 ± 0.72 and 4.04 ± 0.54 milliunits/ml, respectively) due to the presence of RGD sequences attracting more platelets, suggesting their superior haemostatic property (p ≤ .01). Greater amount of platelet interaction was also observed with another NMSF Antheraea mylitta as compared with BMSF owing to RGD sequences in Antheraea mylitta protein supporting our results(Kundu, Schlimp, Nürnberger, Redl, & Kundu, 2014).3.3 | Antibacterial and antibiofilm activity of LL-37 functionalized nanofibrous mats-In vitro and in vivo assayBacterial colonization and biofilm development are commonly observed in diabetic wounds, in response to high glucose environment(Mottola et al, 2016). Bioburden inflicted on chronic wounds, by the presence of polymicrobes, has been evidenced, particularly in the diabetic condition(Martin, Zenilman, & Lazarus, 2010).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…PVAAA and PVAPR showed significantly higher LDH activity (4.32 ± 0.72 and 4.04 ± 0.54 milliunits/ml, respectively) due to the presence of RGD sequences attracting more platelets, suggesting their superior haemostatic property (p ≤ .01). Greater amount of platelet interaction was also observed with another NMSF Antheraea mylitta as compared with BMSF owing to RGD sequences in Antheraea mylitta protein supporting our results(Kundu, Schlimp, Nürnberger, Redl, & Kundu, 2014).3.3 | Antibacterial and antibiofilm activity of LL-37 functionalized nanofibrous mats-In vitro and in vivo assayBacterial colonization and biofilm development are commonly observed in diabetic wounds, in response to high glucose environment(Mottola et al, 2016). Bioburden inflicted on chronic wounds, by the presence of polymicrobes, has been evidenced, particularly in the diabetic condition(Martin, Zenilman, & Lazarus, 2010).…”
supporting
confidence: 80%
“…Bacterial colonization and biofilm development are commonly observed in diabetic wounds, in response to high glucose environment (Mottola et al, ). Bioburden inflicted on chronic wounds, by the presence of polymicrobes, has been evidenced, particularly in the diabetic condition (Martin, Zenilman, & Lazarus, ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Banu et al reported that the predominant biofilm former was Staphylococcus aureus followed by Pseudomonas aeruginosa, Citrobacter species, E. coli, Proteus species and then Klebsiella oxytoca. It was found that polymicrobial communities was able to produce higher biofilm formation than individual species [8]. Kirsner also stated that majority of infections in diabetic wounds are polymicrobial.…”
Section: Causative Organismsmentioning
confidence: 99%
“…Bununla birlikte, kronik yaralarda bulunan mikroorganizmaların çoğunun, özellikle de Pseudomonas ve Staphylococcus gibi türlerin, yüksek düzeyde biyofilm ürettikleri bilinmektedir (41) . Mottola ve ark.…”
Section: Bulgularunclassified